Pengendalian Kualitas Kebocoran Botol Pelumas 800ML dengan 7 Tools - Gustany, Eko Widodo; Haryudiniarti, Ayu Nurul; Hariyanto, AL. (JITMI (Jurnal Ilmiah Teknik dan Manajemen Industri), 2025)
ABSTRACT PT.EFG is a manufacturing company engaged in the production of lubricants for various purposes such as automotive and industry. In order to protect customers from producing quality products, the satisfaction company has implemented good quality control starting from raw materials, packaging materials, production processes to finished goods. In the production process, the company always tries to be able to produce quality products and minimize damage, however, in reality, there are still many products that leak and do not meet the standards set by the company. This study aims to find out how to implement quality control using the seven tools that are useful for controlling the damage level of 800 ml leaking bottles. Problems solved are solved by means of quality control check sheets, pareto charts, histogram charts, stratification, p-chart control charts, scatter charts and fishbone diagrams. Based on data for January-October 2022, results of observations and observations, the biggest cause of leaking bottles is the characteristic of the fish eye leaking sub-attribute, the highest amount of damage occurred in June with a percentage of 0.0039 percent and has exceeded the maximum permissible damage limit of 0.003 percent of the production amount. Judging from the leaking criteria in the form of fish eyes, the improvements that can be made are divided into two, namely external and internal repairs. External repairs at the supplier are cleaning the mold cavity regularly, cleaning the remaining material in the mold, and keeping the plastic pellets clean. implying that the leak tester machine in the production line is working properly and consistently so that leaky bottles can be detected and not sent to PT.EFG. Internal improvements that can be made are repairing the leak detection tool on the led light table machine in the form of adding light. The next improvement is the change in the random sampling method when entering the 800 ml bottle.